An ADDIE-Based Approach to Developing an Automatic Room Sprayer from Recycled Styrofoam Waste - Rindi Nur Wulandari; Hero Wintolo; Adila Aviv Khairunisa; Parhan Parhan; Lasmadi Lasmadi; Emmanuel Endy Ismoyo; Rifky Adhi Pangestu (Compiler, 2026)
Styrofoam waste constitutes an increasingly acute environmental problem in Indonesia due to its non-biodegradable nature and widespread accumulation across various sectors. This study presents the design, development, and evaluation of a proof-of-concept prototype of an Arduino microcontroller-based automatic room sprayer — designated Aero-Spray — that utilizes recycled styrofoam as the primary structural material, shaped into a miniature representation of an Airbus A320-200 aircraft. The system was developed following the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model, which enabled a systematic and iterative development process. The hardware architecture integrates a PIR motion sensor, servo motor, aroma spray module, LCD display, LED indicators, and a buzzer, all coordinated by an Arduino microcontroller. Comprehensive functional testing demonstrated that the PIR sensor reliably detects human movement at distances of up to 6 meters across all evaluated angles (0°, 15°, and 30°). The average system response latency from motion detection to spray activation was 3.8 seconds, while spray interval accuracy attained 98.34% of the programmed value. System power consumption was measured at 1.025 W in idle mode and 4.025 W during active spraying, yielding a total estimated daily energy consumption of 17.42 Wh to 28.16 Wh. Fragrance endurance analysis indicated operational durations of 15 to 24.5 days per 60 mL volume, depending on occupancy levels. These results collectively demonstrate that the Aero-Spray proof-of-concept prototype operates reliably under normal indoor conditions, validating the feasibility of transforming styrofoam waste into a functional, value-added, and environmentally responsible automated device.